The quest for the memory of Jesus : a viable path or a dead end? - Havukainen, Tuomas (Contributions to biblical exegesis and theology, 2020)
"This study is focused on the active international field of study in which various theories of memory (e.g. social/collective memory and individual memory) and ancient media studies (e.g. study of oral tradition and history) are applied to historical Jesus research. The main purpose of the monograph is to study whether the memory approach constitutes a coherent methodological school of thought. The dissertation discusses in what ways the memory approach distinguishes itself from earlier research and whether one can speak of a new beginning in historical Jesus research. A central focus of the study is the research-historical discussion on the nature and processes of the transmission of the Jesus traditions in early Christianity, which is a significant research problem for both earlier historical Jesus research and the memory approach." --back cover